A three-dimensional full-scale model for predicting the performance of deep-buried ground heat exchanger considering groundwater flow. Issue 1 (1st August 2022) - Ma, Z.D.; Jia, G.S.; Zhang, Y.P.; Miao, C.Y.; Xia, Z.H.; Jin, L.W.
Abstract: It is critical to precisely determine the performance of deep-buried ground heat exchangers involving different geological layers in engineering projects of the geothermal energy utilization. Compared to the existing approaches solving only conduction between the ground heat exchanger and the surrounding ground based on the two-dimensional model, this paper established a three-dimensional full-scale coaxial ground heat exchanger model containing both aquifer and aquifuge layers involving groundwater effect. The convective heat transfer in pipes was calculated using the empirical correlation of Nusselt number to improve the computation efficiency. The groundwater velocity in the energy governing equation was assumed to be constant and along with the horizontal direction to further simplify the computation. The developed method was applied to a 2800 m and 2600 m depth ground heat exchangers with different geological conditions, and was validated by the field test and published data. The relative errors are less than 6.9%. The thermal influence ranges of the aquifer layer and the aquifuge layer close to aquifer are asymmetric about the circumferential direction. The results demonstrated that the three-dimensional full-scale model is necessary for accurately evaluating the performance of ground heat exchangers when there is groundwater migration.